The Effects of Coenzyme Q10 on Inflammation Markers in Streptozotocin-Induced Diabetic Rats - Uluisik, Deniz; Keskin, Ercan (Acta Scientiae Veterinariae, 2017)
Background: Coenzyme Q10 is a well-known cofactor in the mitochondrial electron transport chain required for ATP production. Coenzyme Q10 is recognized as an intracellular antioxidant that protects cell membrane phospholipids, mitochondrial membrane protein, and plasma low-density lipoprotein against oxidative damage caused by free radicals. Diabetes and its complications have been related to increased levels of free radicals and systemic proinflammatory cytokines and to an abnormal lipid profile. The aim of this study was to investigate the effects of coenzyme Q10 supplementation on some cytokine levels in streptozotocin-induced diabetic rats. Materials, Methods & Results: In this study, 38 healthy, adult male rats were used. The rats were divided into 5 groups. All animals were housed in separated cages during the four weeks. The animals in group 1 was fed standard rat pellets for 4 weeks. It was administered at 0.3 mL corn oil intraperitoneally daily for four weeks in group 2 animals. The animals in group 3 was injected intraperitoneally with 10 mg/kg CoQ10 daily for 4 weeks. Group 4 was made diabetic by subcutaneous injections of streptozotocin at dose of 40 mg/kg in 0.1 M citrate buffer (pH 4.5) single daily dose for two days and group 5 was made diabetic by subcutaneous injections of streptozotocin at dose of 40 mg/kg in 0.1 M citrate buffer (pH 4.5) single daily dose for two days and then was injected intraperitoneally with 10 mg/kg CoQ10 daily for 4 weeks. During the experiment, three animals from group 4 and one animals from group 5 were died due to streptozotocin-induced hypoglycemia. At the end of the study, blood samples were taken from all animals. In these blood samples, IL-4, IL-6, IL-10 and TNF-α plasma levels were determined with ELISA using sandwich enzyme-linked immunosorbent method via commercial kits. In this study, IL-4 level as an anti-inflammatory cytokine significantly decreased (P < 0.05) with diabetes induction compared to control group level. IL-10 level in diabetic group was statistically different (P < 0.05) from control group level. CoQ10 application to diabetic animals improved the falling in IL-10 level of diabetic group (P < 0.05). IL-6 and TNF-α levels in diabetic group significantly increased (P < 0.05) in parallel with each other compared to control group levels. The same parameters were reduced (P < 0.05) by CoQ10 application in diabetic animals. Discussion: In this study, the occurred changes in pro- and anti-inflammatory cytokines with experimentally induced diabetes are expected results and these results are consistent with some studies related diabetes. These results may be considered to hazardous effects and inflammation caused by diabetes on liver, pancreas and other tissues. CoQ10 suppressed the increments in plasma pro-inflammatory cytokine levels, whereas it restored the reducing in anti-inflammatory cytokine levels arising due to diabetes. The obtained results from this study after CoQ10 application supported similar studies used CoQ10 application against deleterious effects of diabetes in animals and humans. Therefore, it is possible to say that CoQ10 may play important role in regulation of imbalance between inflammation markers in diabetes conditions and further studies are needed to clear the beneficial effects of CoQ10 treatment on the other inflammation markers in diabetes status.